COMBATTING METHICILLIN-RESISTANT STAPHYLOCOCCUS AUREUS (MRSA) IN THE FOOD INDUSTRY BY HARNESSING THE POWER OF NATURE: A SYSTEMATIC REVIEW - Zahra Alinezhad; Mohammad Hashemi; Asma Afshari; Golshan Shakeri (Archives of Veterinary Medicine, 2023)
Antibiotic resistance is a critical global health concern, with Methicillin-resistant Staphylococcus aureus (MRSA) posing a significant challenge due to its resistance to commonly used antibiotics. Recent research has revealed the potential of natural compounds and microorganisms in combatting MRSA and other antibiotic-resistant bacteria. In this systematic review, we studied the effect of essential oils, bacteriophages, bacteriocins, and probiotics on S. aureus, including MRSA in particular, in the food industry. Essential oils (EOs) have gained significant attention because of their antimicrobial properties, inhibiting MRSA growth by damaging bacterial cells and inhibiting essential enzymes and compounds. Cinnamon oil liposomes caused the most significant decrease in MRSA populations among our reviewed essential oils. Bacteriophages can lyse the bacterial host. They encode peptidoglycan hydrolases called endolysins that target the bacterial cell wall. In our study, S. aureus phage (containing CHAPLysGH15 and LysGH15), and phage SA11 endolysin (LysSA11) were the most effective against S. aureus. Bacteriocins, antimicrobial peptides produced by bacteria, also show potential in combatting MRSA, mainly by generating organic acids that interfere with bacterial metabolism. According to our review, the most effective bacteriocins against S. aureus were Enterocin AS-48 with phenolic compounds or with 2NPOH, Bacteriocin isolated from Lactobacillus pentosus - Pentocin JL-1, and bacteriocin produced by S. pasteuri RSP-1, respectively. Probiotics can compete with pathogens by producing antimicrobial compounds that disrupt MRSA cell production and ultimately lead to bacterial death. In our review, the most effective probiotics were Streptomyces griseus, Pediococcus acidilactici strains A11 and C12, Lactococcus lactis, and Lactobionic acid respectively. A multi-hurdle approach combining these natural agents has shown promising results in targeting and eliminating MRSA cells. By harnessing the power of nature, we can potentially overcome the challenges posed by MRSA and other antibiotic-resistant bacteria.